2004
DOI: 10.1038/nature02874
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing in plants

Abstract: There are at least three RNA silencing pathways for silencing specific genes in plants. In these pathways, silencing signals can be amplified and transmitted between cells, and may even be self-regulated by feedback mechanisms. Diverse biological roles of these pathways have been established, including defence against viruses, regulation of gene expression and the condensation of chromatin into heterochromatin. We are now in a good position to investigate the full extent of this functional diversity in genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
1,667
0
66

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,272 publications
(1,745 citation statements)
references
References 83 publications
12
1,667
0
66
Order By: Relevance
“…The role of dsRNA in triggering repression was initially characterized in Caenorhabditis elegans and termed RNA interference (Fire et al 1998). However, silencing phenomena had already been described in a number of eukaryotes and the connection to dsRNA helped to unify several, apparently disparate, processes involving post-transcriptional RNA degradation, transcriptional gene silencing via heterochromatin formation and/or DNA methylation, DNA elimination, or meiotic silencing by unpaired DNA (Baulcombe 2004;Matzke and Birchler 2005;Ullu et al 2004;Zamore and Haley 2005). In plants and animals, the RNAi machinery is also involved in the production of microRNAs (miRNAs), by the processing of genome encoded imperfect RNA hairpins, which play a role in developmental regulation (Bartel 2004;Wienholds and Plasterk 2005;Zamore and Haley 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of dsRNA in triggering repression was initially characterized in Caenorhabditis elegans and termed RNA interference (Fire et al 1998). However, silencing phenomena had already been described in a number of eukaryotes and the connection to dsRNA helped to unify several, apparently disparate, processes involving post-transcriptional RNA degradation, transcriptional gene silencing via heterochromatin formation and/or DNA methylation, DNA elimination, or meiotic silencing by unpaired DNA (Baulcombe 2004;Matzke and Birchler 2005;Ullu et al 2004;Zamore and Haley 2005). In plants and animals, the RNAi machinery is also involved in the production of microRNAs (miRNAs), by the processing of genome encoded imperfect RNA hairpins, which play a role in developmental regulation (Bartel 2004;Wienholds and Plasterk 2005;Zamore and Haley 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, putative homologs of a tomato RdRP are required for post-transcriptional gene silencing (PTGS) triggered by sense transgenes in A. thaliana, for quelling (a phenomenon similar to PTGS) and for meiotic silencing by unpaired DNA in Neurospora crassa, as well as for RNAi in C. elegans and Dictyostelium discoideum (Baulcombe 2004;Cogoni and Macino 2000;Martens et al 2002;Shiu et al 2001;Sijen et al 2001;Wassenegger and Krczal 2006). It has been proposed that RdRPs generate dsRNA from single-stranded transcripts either by de novo, primer independent second-strand synthesis (utilizing as template "aberrant" RNAs, presumably lacking normal processing signals such as a 5′ cap or a polyA tail) or by using siRNAs as primers to synthesize RNA complementary to the target mRNA (Baulcombe 2004;Sijen et al 2001;Wassenegger and Krczal 2006). Thus, RdRP activity may initiate RNAi (by producing the trigger dsRNA) or dramatically enhance the RNAi response (by amplifying the amount of dsRNA) (Baulcombe 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal small ribonucleic acids (RNAs) of 20–40 nucleotides (nt) are involved in RNA-silencing, which can regulate the expression of target genes and therefore are involved in a variety of biological processes, such as development, antiviral defence and the maintenance of genomic stability (Brennecke et al 2003; Sijen and Plasterk 2003; Baulcombe 2004; Lu et al 2005). Based on their RNA precursors and biogenesis mechanisms, these small RNAs can be divided into various types in fungi, including QDE-2-interacting small RNAs (qiRNAs), microRNA-like RNAs (milRNAs), Dicer-independent small interfering RNAs (disiRNAs), small interfering RNAs (siRNAs), long terminal repeat retrotransposon-siRNAs (LTR-siRNAs) and tRNA-derived RNA fragments (tRFs) (Jöchl et al 2008; Lee et al 2009; Nicolas et al 2010; Nunes et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results in mammals suggest a role of RNAi in trans criptional gene silencing through the targeting of promoter regions (Han et al, 2007) and -in the February issue of EMBO reports-the Allshire group showed that Schizo saccharomyces pombe can repress gene expression through a trans effect that is reminiscent of mammalian post-transcriptional gene silencing (Fig 1; Simmer et al, 2010). Both transcriptional gene silencing and post-transcriptional gene silencing are also well known to coexist in plants (Baulcombe, 2004).…”
mentioning
confidence: 99%